Effect of Guava Juicy (Psidium guajava L.) Addition on Organoleptic Properties of Tempeh Yoghurt - Cita Eri Ayuningtyas; Waluyo Waluyo; Susetyowati Susetyowati (Study Program of Nutrition, Public Health Faculty, Institut Kesehatan Helvetia, 2018)
Tempeh yoghurt is one of functional food modified by tempeh. Yoghurt is recogniced as a healthy food. Tempeh yoghurt clinically proven reduce cholesterol, despite of its appearance still needs development. Therefore, tempeh yoghurt needs improvement to increase its appearance. Objectives; to prove the relationship of organoleptics of tempeh yoghrut and the additions of guava juicy. Material and Method; type of research used experimental, four variations of guava juicy added to tempeh yoghurt : 5%, 10%, 15% and 0% as a control. 20 panelis gave level of pleasure of organoleptics of tempeh yoghurt. Result of the research analyzed by Kendall’s and would be continue to Wilcoxon test. Results; Addition of guava juicy was’not related to panelis preferences of the color’s tempeh yoghurt (p=0,420), taste (p=0,156), flavor (p=0,297), viscosity (p=0,988) and all the properties (p=0,166). Conclusion; it was found that there wasn’t a correlation between addition of guava juicy and organoleptics properties of tempeh yoghurt.